Age at menarche among Iraqi adolescent in Baghdad 2017 - Al-Kaseer, Eman A.; Ismail, Raghda A. (Technium BioChemMed, 2022)
Background: Menarche is a biological trait affected by several factors (genetic parameters, socioeconomic conditions, general health, and lifestyle, nutritional status, seasonality, physical activities, and level of education). Exposure to wars and conflicts are factors affecting menarche, too. Iraqi population was exposed to wars and conflicts, this study was planned to demonstrate the effect of wars and conflicts on menarche. Methods: A total of 444 female intermediate school students was included in the study. They were recruited by multistage random sampling technique (one side of Baghdad of the two was selected randomly, one educational directorate out of the 3 directorates was selected randomly, 4 intermediate schools were selected out of 9 intermediates at the selected directorate were chosen randomly, one class of the chosen schools was selected randomly, then one class from each school was selected randomly). An interview was carried out with each student in the selected class. The requested information was demographic data, age at menarche, crowing index (household divided by number of room), physical activity and body mass index. Results: Age at menarche was 11.8 ± 1.8 year. Crowding index was positively affected age at menarche (p=0.01). Weight was negatively affected age of menarche (p=0.000). Age at menarche was positively associated with active female and / or athlete female (p=0.0001). Watching reality or horror movies was associated with low age at menarche (p=0.0001). Practicing video games was associated with low age at menarche (p=0.0001). Chronic diseases were associated with increase age at menarche (p=0.03). Exposure to violence was associated with low age at menarche (p=0.0001) Conclusion: Age at menarche was 11.8 ± 1.8 year. Socioeconomic status, weight, physical activity, watching horror movies and playing videogames were affecting age at menarche.